Mechanical and Surface Properties of Edible Coatings Elaborated with Nanoliposomes Encapsulating Grape Seed Tannins and Polysaccharides - Vega-Viveros, R; Osorio-Lira, F; Monasterio-Aranda, A (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Edible composite coatings (ECC) formulated from biopolymers that incorporate antioxidant molecules represent an innovative alternative to improve food texture and provide health benefits. Tannins have aroused great interest due to their ability to stabilize suspensions and counteract the effects of free radicals. The mechanical and surface properties are crucial to establishing its quality and applicability. In this study, the objective was to analyze the mechanical and surface properties of ECC made with nanoliposomes that encapsulate grape seed tannins (TLS) and polysaccharides such as hydroxypropylmethylcellulose (HPMC) and kappa carrageenan (KCG) for their future direct application in foods susceptible to oxidation. The inclusion of HPMC or KCG affected the density, showing values in the range of 1010 to 1050 [kg/m3], evidencing significant changes (p < 0.05) in the surface tension in the TLS/FS-HPMC and TLS/FS mixtures. KCG and in the dispersion coefficients, with values in the range of −2.9 to −17.6 [mN/m] in HPS (S1) and −17.6 to −40.9 [mN/m] in PDMS (S2). The TLS/FS-HPMC coating showed higher stiffness and elastic recovery capacity than the TLS/FS-KCG coating, suggesting that the presence of TLS influenced the stiffness of the polymer. HPMC is recommended as a suitable polymer for coating solids, while KCG is more appropriate for suspensions. These findings provide valuable information for directly applying these ECC compounds to food products, potentially offering better preservation and health benefits. © 2023 by the authors.